Chronic Intake of Red Palm Olein and Palm Olein Produce Beneficial Effects on Plasma Lipid Profile in Rats - Kamisah, Y.; Adam, A.; Ngah, W.Z. Wan; Gapor, M.T.; Azizah, O.; Marzuki, A. (Pakistan Journal of Nutrition, 2005)
Palm olein (PO) and red palm olein (RPO) are rich in tocopherols and tocotrienols. In addition, RPO also contains a high content of carotene. This study was to determine the effect of chronic intake of diets containing palm oils, varying in their vitamin E and carotene contents, on lipid profile in rats. Weaning male Wistar rats were fed either 18% RPO, 18% PO or 18% vitamin E-stripped palm olein (SPO) for 12 weeks. Plasma total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL) and low density lipoprotein cholesterol (LDL) were measured at weeks 4, 8 and 12. Feeding the different types of palm oil did not affect TC and HDL from week 4 through week 12, but there were reductions in TG in all dietary groups at week 12 compared to week 4 but differences between groups were not observed. The RPO group had lower LDL at week 12 (vs weeks 4 and 8) but LDL was not reduced in the PO and SPO groups. TC/HDL was reduced in the RPO group at week 12 compared to both weeks 4 and 8, but the PO group only reduced this ratio at week 12 compared to week 4. This finding suggests that chronic feeding of diets high in palm oils did not cause any detrimental effects on blood lipid profile. In addition, red palm olein which is rich in antioxidants in the forms of vitamin E and carotene, showed better effect in terms of reduction in LDL and TC/HDL.